The Effect Of Corporate Debt And Profitability On Corporate Intrinsic Value In Banking Companies In Indonesia - Humiras Sidabutar; Rina Br. Bukit; Nazaruddin Nazaruddin; Khaira Amalia F; Handy Oktavianus (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The Aim of this study is to look into how capital structure affects the true value of a company. Amounts of short-term debt to total assets (STDTA), long-term debt to total assets (LTDTA), and total debt to total assets (TDTA) show how much of an effect this has. The return on equity (ROE) ratio is another way to measure the effect of revenue. The net present value of the expected Free Cash Flow to Equity (FCFE) tells us how much the company is really worth. This study is mostly about companies that were launched on the Indonesia Stock Exchange between 2017 and 2019. Out of the 44 companies that exist, 26 were picked to be part of the study. The path analysis method was used to test the hypothesis at a significance level of 5%. The results show that STDTA has a significant positive effect of 0.068 on the company's intrinsic value. This means that a one-time increase in short-term debt compared to total assets will raise the intrinsic value by 6.8%. The company's fundamental value goes up by 0.05, which is a noticeable amount. On the other hand, TDTA has a big negative effect of -0.968, which means that a one-time rise in total debt compared to total assets will lower the value by 96.8%. Finally, profitability through ROE showed a strong positive effect of 0.773, which means that a one-time increase in net profit compared to total stock will raise the value by 77.3%.